The achievement of students often taking selfies of the eleventh-grade students at SMKS Perwari Tulungagung - Yulia Nugrahini (Concept : Community Concern for English Pedagogy and Teaching, 2022)
In this study, the researcher wanted to prove whether the students who often take selfies get lower achievement than the students who do not often take a selfie at SMKS Perwari Tulungagung in the 2020/2021 academic year. The researcher used an ex-post-facto experimental design that was categorized into quantitative research. This study was conducted at SMKS Perwari Tulungagung. The population of this study was all students of eleventh grade at SMKS Perwari Tulungagung in the 2020/2021 academic year which consist of 320 students and the sample was taken randomly 15% about 48 students. The finding of this study can be seen that the average score of the experimental group was 84 and the control group was 85. It means that the experimental group got a lower score than the control group. Then, after the researcher analyzed the data by using the t-test formula, the researcher got the result t count was 2.557 by a significant level of 0.05 and df= n-2 = 48-2=46, and the t table is 2.013. Finally, it proved that the students who often took selfies got lower achievements than the students who did not often take a selfie on the students' achievement at SMKS Perwari Tulungagung in the 2020/2021 academic year. Key Words: Taking selfies; achievements;